2012
DOI: 10.1016/j.mayocp.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Laboratory Testing to Guide Antimicrobial Therapy

Abstract: Antimicrobial susceptibility testing (AST) is indicated for pathogens contributing to an infectious process that warrants antimicrobial therapy if susceptibility to antimicrobials cannot be predicted reliably based on knowledge of their identity. Such tests are most frequently used when the etiologic agents are members of species capable of demonstrating resistance to commonly prescribed antibiotics. Some organisms have predictable susceptibility to antimicrobial agents (ie, Streptococcus pyogenes to penicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 106 publications
3
136
0
4
Order By: Relevance
“…Phenotypic antibiotic susceptibility tests (ASTs) are typically based on the detection of differential bacterial growth with and without antibiotics in liquid cultures or on solid agar plates (4). In liquid tests, detection is based on the change in OD, whereas the disk diffusion method is used on solid agar plates to identify inhibition zones (5).…”
mentioning
confidence: 99%
“…Phenotypic antibiotic susceptibility tests (ASTs) are typically based on the detection of differential bacterial growth with and without antibiotics in liquid cultures or on solid agar plates (4). In liquid tests, detection is based on the change in OD, whereas the disk diffusion method is used on solid agar plates to identify inhibition zones (5).…”
mentioning
confidence: 99%
“…Turbidity of pipe created by bacteria growth in the culture medium reported as +2, + 1 and -(minus) and power-plate was done in the MRS Agar and Mueller Hinton Agar culture medium [11][12][13][14][15][16].…”
Section: Salt Tolerance Testmentioning
confidence: 99%
“…Clinical studies show that Lactobacillus cells in in vitro conditions can decrease added cholesterol to the culture medium and in in vivo conditions also can reduce serum cholesterol. Jenkins [15] showed that increase of lipid in culture medium reduces the synthesis of lipid acids by lactic acid bacteria [20]. The findings indicate that probiotics are capable of absorbing cholesterol into their cell membranes in the presence of bile [23].…”
Section: Antibiotic Diskmentioning
confidence: 99%
“…Studies on hospital-acquired infections have also claimed the involvement of multidrug-resistant bacteria, and the recent emergence of carbapenem resistance has amplified the phenomenon (Khan et al, 2012;Theuretzbacher, 2012;Cohen, 2013). Consequently, an early diagnosis of resistant clinical isolates is key information for the clinician to select an appropriate treatment (Jorgensen & Ferraro, 2009;Orenga et al, 2009;Jenkins & Schuetz, 2012;Bhattacharya, 2013;Laxminarayan et al, 2013). Today, it is well recognized that the first step of antibiotic use is a key action that can govern the fate of the infection by selecting or rendering the bacteria more resistant via their adaptive response and resistosome (Schuldiner, 2009;Bhattacharya, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the time required for microbial identification and susceptibility tests represents a challenge and needs continuous improvement of methods, selected media and interpretation of raw data (Jorgensen & Ferraro, 2009;Jenkins & Schuetz, 2012;Bhattacharya, 2013). This detection is often carried out by automated systems that are based on early growth detection in an appropriate antibiotic containing medium that may differ in nutrients from the MuellerHinton (MH) reference medium (Livermore et al, 2002;Lee et al, 2008;Pitout et al, 2008;Jorgensen & Ferraro, 2009;Orenga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%